Agri-food 4.0 : innovations, challenges and strategies - Mohr, Rahul S.; Kumar, Dinesh; Singh, Anupama (Bingley, U.K. : Emerald Publishing Limited, 2022)
The Agri-Food industry currently faces a range of challenges, from food safety and security, demand, and supply gaps to the maintenance of product quality and issues in product traceability. Smart digital technologies have opened a complete paradigm shift, providing solutions to these challenges, and helping move towards safe, resilient, responsive, and eventually profit-driven supply chains. The use of these digital technologies by Agri-Food supply chains can bring significant changes in food supply chain management by reducing food wastage, real-time product monitoring, and reducing scalability issues. Agri-Food 4.0: Innovations, Challenges and Strategies addresses new research on digital technologies in the industry, including smart packaging, smart warehousing, effective inventory control, blockchain technology, artificial intelligence, and other Industry 4.0 concepts. Agri-Food 4.0 explores the challenges and complexities in implementing such technologies, helping policymakers in the agri-food sector with impact assessment and digital transformation towards creating a sustainable industry.
Chapter 1. Research trends and innovation perspectives about sustainability and agri-food 4.0 / Capobianco Uriarte Maria de Las Mercedes, Cravero Ricardo, Regodesebes Alejandro, Grabois Marcelo, and Casado Belmonte Maria Pilar -- Chapter 2. Digital technology: Implementation challenges and strategies in agri-food supply chains / Priyanka Vern, Naema Miftah, and Anupama Panghal -- Chapter 3. Modelling the challenges for agri-food supply chain 4.0: Tism approach / Shilpa Sindhu and Rupesh Kumar -- Chapter 4. An overview for food loss and waste reduction in food supply chains / Banu Y. Ekren and Vikas Kumar -- Chapter 5. Technological advancement and circular economy practices in food supply chain / Syed Abdul Rehman Khan, Muhammad Umar, Hafiz Muhammad Zia-ul-haq, and Zhang Yu -- Chapter 6. Blockchain-based smart wheat supply chain model in Indian context / Shobha Rathore, Nainsi Gupta, A.P.S. Rathore, and Gunjan Soni -- Chapter 7. Drone based crop product quality monitoring system: An application of smart agriculture / Altaf Alam, Anurag Chauhan, Mohd Tauseef Khan, and Zainul Abdin Jaffery -- Chapter 8. Overview of iot in the agro-ecosystem / Mehul Parmar and Ranjan Kumar -- Chapter 9. Smart irrigation system using iot / Amit Kumar, Praful Ranjan, and Vaibhav Saini -- Chapter 10. Digital transformation: Artificial intelligence (ai) based product benefits and problems of agritech industry / C. Ganeshkumar, Arokiaraj David, and D. Raja Jebasingh -- Chapter 11. Advancement in packaging technologies for agri-food sector / Priyanka Dubey, Owais Yousuf, and Anupama Singh -- Chapter 12. Industry 4.0 technologies in agri-food supply chains: Key performance indicators / Rohit Sharma -- Chapter 13. Robotics and automation for agri-food 4.0: Innovation and challenges / Rahul S Mor, Dinesh Kumar, Anupama Singh, Neethu K.
Includes index.
Keywords: Agricultural processing industries; Industry 4.0.; Business & Economics -- Industries / Agribusiness; Agriculture & related industries